Rationale for Why and How We Teach our Capstone/Senior Seminar - Smith, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
A seminar for senior sociology majors, which endeavors to crystallize the student’s knowledge,skills, and appreciation of the discipline. This is a capstone course designed to assist students in synthesizing material from other sociology courses, particularly theory and research methods, by using Mills’ notion of the Sociological Imagination to inform their sociological perspective.